Analysis of Cold Chain Product Management in Community Health Centers in Siak Regency Based on Their Accreditation Level - Putri, Monica Rifa; Husnawati, Husnawati; Sari , Seftika (Jurnal Indonesia Sosial Sains, 2025)
This study aims to analyze the management of cold chain products in primary health centers (Puskesmas) across Siak Regency based on their accreditation levels. The research is motivated by the high rate of cold chain management deviations that may compromise the quality and effectiveness of medicines, particularly vaccines. A mixed-method approach with a sequential explanatory model was applied, involving all 16 Puskesmas as the total sample. Quantitative data were collected through observations using the 2020 CDOB checklist, while qualitative data were obtained from in-depth interviews with cold chain officers. Data analysis employed the Chi-Square test to examine the relationship between accreditation levels and cold chain management quality. The results revealed a significant relationship between accreditation status and management quality, especially in facility compliance, SOP adherence, maintenance, and calibration standards. Highly accredited Puskesmas (paripurna and utama) demonstrated “good” to “very good” management performance, whereas non-accredited facilities remained in the “fair” category or lower. These findings highlight accreditation as a key determinant of effective cold chain management. The study underscores the need for continuous training, improved infrastructure, and enhanced monitoring systems to ensure the quality of cold chain medicines in primary health services.